p53 destabilizing protein skews asymmetric division and enhances NOTCH activation to direct self-renewal of TICs - Hye Yeon Choi (Nature Portfolio, 2020)
Normal stem cells are maintained by asymmetric cell division, but this process is dysregulated in tumour initiating stem-like cells (TICs). Here, the authors show that TBC1D15 impairs the asymmetric division machinery and activates NOTCH pathway for TIC self-renewal and expansion to promote liver tumorigenesis.